EMPLOYEE PERFORMANCE AFFECTED BY WORK ROTATION AND TRAINING - Bintang Narpati; Difa Mulki Sabila; Wastam Wahyu Hidayat; Rorim Panday; Elia Rossa (Jurnal Ilmiah Akuntansi dan Manajemen, 2022)
This study aims to determine simultaneously and partially the independent variables, namely the Job Rotation and Training to dependent variable, namely employee performance. This research was conducted at PT Bank Syariah Indonesia, Area Bekasi. In this study using a quantitative approach and data analysis used, namely the classical assumption test and multiple linear regression analysis, to test and prove the research hypothesis using the SPSS version 23 application. The population in this study were all employees of PT Bank Syariah Indonesia, Area Bekasi in the finishing section as many as 100 people. Trough testing the coefficient of determination obtained a value of 0,620 it means 62,0%. Variable of Employee Perfomance can be explained by variables Job Rotation and Training while the remaining 38,0% can be explained by other variables not examined in this study. Partially the job rotation variable has a significant influence on employee performance with t-count > t table partially the results of the Training variable have a significant effect on employee performance with t-value > t-table. Meanwhile, based on the simultaneous test results obtained from this study on the Job Rotation and Training variables, the results of the calculated F value > F table.